Modifikasi Penambahan Inverter Pada Mesin Slicing Menggunakan Sistem Penggerak Motor Listrik - Arif Cahyono, M Ridwan; Andre; Christiano Doni, Benedictus (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2025)
Quality control in cable manufacturing is important to guarantee product reliability. The use of semi-automated machines, such as electric motor-powered slicing machines, is essential in creating test specimens.Existing cutting machines have limitations, such as a fixed speed, which slows down the cutting process. This study improves the efficiency of the slicing machine by using an inverter to regulate the frequency and speed of the motor. The inverter with a frequency of 127-135 Hz reduced the cutting time from 28 seconds to 10.28-9.69 seconds.The 370 W motor produces 2.52 Nm of torque, which is converted to 75.6 Nm at the output of the gearbox with a ratio of 1:30. With a gearbox efficiency of 90%, the available torque on the blade is 68.04 Nm at a speed of 4.89 rad/s, resulting in an effective power of 332.73 W. This modification is powerful enough to slice cable insulation according to specifications.